Water Quality Of Lake Toba By Space And Time Based On Environmental Physics, Chemical Factors And Community Phytoplankton - Rahman Rahman; Mustaji Mustaji; Bachtiar S. Bachri; Muhamad Suhardi (Green Publisher Indonesia, 2022)
This study aims to develop a multicultural learning model for Primary Teacher Education as well as learning strategies, materials, media, and manual lectures based on the modified model (MPI). The research was carried out from March 2018 to April 2019 and took place at the primary education laboratory of the Education office of East Lombok. The results of the research were based on the evaluation. First of all, the evaluation from the experts' review stated that the developed model was ready to be used for testing after it was improved based on experts’ input, secondly, the evaluation was based on one-on-one test, small-group test, and field test. There were 60 respondents involved and the validity of the data was taken by using data triangulation techniques. The results of this research showed that learning activities in the classroom become more interesting, systematic, so that students were easy to understand it. The use of video within the activities became more attractive for students because it suits the situation they face, as well as helping them easier to understand the materials. Evaluation tools were relevant to the material, so students can think critically and reflectively. The developed modules were easy to understand, and the independent learning activities contained in the modules can be followed so that the learning objectives were achieved. The lecturer guide was very helpful for lecturers in implementing multicultural education in the classroom setting.